ANALISIS PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BAGIAN KEUANGAN DINAS KESEHATAN KABUPATEN PONOROGO - kristian, zovan (Universitas Slamet Riyadi, 2020)
The quality of work environment has an important role in performance, to achieve appropriate and effective job performance and efficiency, each organization discusses how to create an environment that is beneficial for employees to achieve higher levels of ability in their work. In addition to the work environment, motivation is also one of the factors that support the performance. Motivation pushes people towards actions that help them achieve maximum performance. The purpose of this study is to study the factors that affect the performance of employees in Dinas Kesehatan Ponorogo Regency in terms of 2 variables, which are work environment and work motivation. The population of this study is 37 people and 37 sampel with a sampling method using saturated sampling. Analysis of the data used is multiple regression analysis. The calculation results test the significance value of the work environment variable is 0,762 which means that the work environment variable is not significant on performance. While the motivation variable has a significance value of 0,001 which means that the motivation variable is significant on performance. While the F test obtained a significance value of 0,001 can be concluded as a variable Work environment and motivation together are significantly positive towards performance by 35,1%. This research proves that not all proposed hypotheses are proven empirically. Motivation is proven to support employee performance, but the work environment does not affect. From the theory with the results of many research factors that cause differences in research results one of which is the selection of indicators in measuring the work environment.Â Keywords: work environment, motivation, performance